Correlation of Interleukin-10, Superoxide Dismutase (SOD), and Malondialdehyde (MDA) Levels with HbA1c in Pediatric Type 1 Diabetes Mellitus - Lina Astari; Haryudi Cahyono; Edi Widjajanto (Journal of Tropical Life Science, 2017)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease characterized by pancreatic Î²-cell destruction and considered to be correlated with oxidative stress. This study aimed to investigate the association of oxidative stress [superoxide dismutase (SOD) and malondialdehyde (MDA) levels], inflammation [interleukin 10 (IL-10)], and glycemic control (HbA1c) in pediatric T1DM patients. This study included 25 T1DM subjects and 25 healthy control subjects and was designed as a cross- sectional study. SOD, MDA, and IL-10 levels were measured by ELISA. We obtained that that IL-10 and SOD levels were significantly decreased in the T1DM group, but MDA and HbA1c levels were significantly elevated in the T1DM group. IL-10 levels were positively correlated with SOD levels and negatively correlated with MDA and HbA1c. SOD levels were negatively correlated with HbA1c levels. MDA was positively correlated with HbA1c levels. IL-10 and SOD levels were significantly decreased, but MDA and HbA1c levels were significantly elevated in the T1DM group.